2019
DOI: 10.1089/jwh.2018.7070
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Patients' Perspectives and Information Needs Following a Positive Home Human Papillomavirus Self-Sampling Kit Result

Abstract: Objective: We explored patient perspectives after a positive human papillomavirus (HPV) self-sampling result to describe experiences and information needs for this home-based screening modality. Materials and Methods: We recruited women who tested high-risk (hr) HPV positive during a pragmatic trial evaluating mailed hrHPV self-sampling kits as an outreach strategy for women overdue for Pap screening in a U.S. integrated health care system. Telephone interviews were conducted from 2014 to 2017. Five independen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
38
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(47 citation statements)
references
References 32 publications
(41 reference statements)
8
38
1
Order By: Relevance
“…'Relief' was also endorsed by 27.4%, 'encouraged' endorsed by 35.9%, and 'in control' endorsed by 68% of HPV-positive women in a descriptive study (Daley et al, 2010). Ten qualitative studies reported positive emotions such as relief, increased trust and acceptance, though they were minor themes (Barrera-Clavijo et al, 2015;Head et al, 2017;Kosenko et al, 2012;Lin et al, 2011;Linde et al, 2019;McCaffery & Irwig, 2005;Perrin et al, 2006;Tiro et al, 2019;Waller, McCaffery, et al, 2007;Wyndham-West et al, 2018). Women who reported positive emotional responses to their HPV results described receiving their test results in person by a healthcare professional, consulting with a healthcare professional after results, having a supportive partner and/or mobilising social support.…”
Section: Positive Affect (Relief Acceptance)mentioning
confidence: 99%
See 4 more Smart Citations
“…'Relief' was also endorsed by 27.4%, 'encouraged' endorsed by 35.9%, and 'in control' endorsed by 68% of HPV-positive women in a descriptive study (Daley et al, 2010). Ten qualitative studies reported positive emotions such as relief, increased trust and acceptance, though they were minor themes (Barrera-Clavijo et al, 2015;Head et al, 2017;Kosenko et al, 2012;Lin et al, 2011;Linde et al, 2019;McCaffery & Irwig, 2005;Perrin et al, 2006;Tiro et al, 2019;Waller, McCaffery, et al, 2007;Wyndham-West et al, 2018). Women who reported positive emotional responses to their HPV results described receiving their test results in person by a healthcare professional, consulting with a healthcare professional after results, having a supportive partner and/or mobilising social support.…”
Section: Positive Affect (Relief Acceptance)mentioning
confidence: 99%
“…Seventeen papers were quantitative studies (Alay et al, 2019;Andreassen et al, 2019;Ferenidou et al, 2012;Garces-Palacio et al, 2019;Hsu et al, 2018;Kitchener et al, 2008;Kwan et al, 2011;Maggino et al, 2007;Maissi et al, 2004Maissi et al, , 2005McBride et al, 2020;McCaffery et al, 2004;Nagele et al, 2019;Ngu et al, 2018;Rodriguez et al, 2019;Wang et al, 2010;Wang et al, 2011), 15 were qualitative (Barrera-Clavijo et al, 2015;Barreto et al, 2016;Bertram & Magnussen, 2008;Head et al, 2017;Kosenko et al, 2012;Lin et al, 2011;Linde et al, 2019;McCaffery & Irwig, 2005;McCaffery et al, 2006;McCurdy et al, 2011;O'Connor et al, 2014;Perrin et al, 2006;Tiro et al (2019); Waller, McCaffery, et al, 2007;Wyndham-West et al, 2018) and one was mixed-methods (Daley et al, 2010). A total of 12,789 women aged between 18 and 65 participated in twenty studies (n=12,244 quantitative; n=545 qualitative), of whom 4,305 were reported as having tested positive for HPV (n=3,874 quantitative; n=431 qualitative).…”
Section: Study Characteristicsmentioning
confidence: 99%
See 3 more Smart Citations